Effectiveness of a Specially Designed Dental Model for Training, Evaluation, and Standardization of Pocket Probing. Issue 12 (1st December 2016) - Sunaga, Masayo; Minabe, Masato; Inagaki, Koji; Kinoshita, Atsuhiro
Abstract : The aim of this study was to evaluate the effectiveness of a dental model in training, evaluation, and standardization of examiners in pocket probing and to determine the appropriate thresholds of accuracy and measuring time when using this model for evaluation of probing skills without measuring patients' pockets repeatedly. In 2011–12, a total of 66 dental professionals and 20 dental students in Japan measured the probing depths of 24 artificial teeth using the six‐point method on a dental model. All examiners measured the probing depths of six tooth groups and then checked the correct depths in each group. Each examiner measured four groups in a group‐by‐group manner. For each group, the measuring time and examiner's accuracy were recorded. Receiver operating characteristic (ROC) curves for various thresholds of measuring time were drawn for thresholds of accuracies to determine the passing mark as a skilled examiner. The accuracy significantly increased from the first to the fourth measurements, and the measuring time was significantly reduced for both the professionals and students. The total measuring time was significantly longer for the students than the professionals. The students' accuracy was significantly lower than that of the professionals in the first measurement group. The increasing rate of accuracy was significantly higher for the students than the professionals. These results and ROC curves suggested that the dental model is effective for periodontal pocket probing training and for the evaluation and standardization of examiners' probing skill at a preclinical level. An examiner having accuracy ≥80% within four minutes for six tooth measurements in this model could be considered a skilled examiner.